2016
DOI: 10.1111/ecpo.12071
|View full text |Cite
|
Sign up to set email alerts
|

Political Leaders' Socioeconomic Background and Public Budget Deficits: Evidence from OECD Countries

Abstract: This paper empirically analyzes the relationship between political leaders' socioeconomic backgrounds and public budget deficits utilizing panel data on 21 OECD countries from 1980 to 2008. Building on sociological, as well as economic research, we argue that the socioeconomic status of political decision‐makers, i.e., presidents or prime ministers, is an important determinant of fiscal budget decisions. Our theory‐consistent findings show that the tenures of lower‐class leaders – i.e., leaders of low socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…And while the partisanship of the political leadership has received much attention, the background of the political leadership has not been featured in these empirical studies as a potential influencing factor for policy responses. This is notable since the background of political leaders has been found to be a significant factor for, for instance, the level of a country's budget deficit (Hayo and Neumeier, ), the willingness to adopt reforms, specifically liberalization (Dreher et al ., ), and its preferences with regard to monetary policy (Göhlmann and Vaubel, ). Investigating whether the background of the political leadership makes reform more or less likely in times of crisis might open up a promising area of research.…”
Section: Methodological Operationalization Of the Crisis Hypothesis –mentioning
confidence: 99%
“…And while the partisanship of the political leadership has received much attention, the background of the political leadership has not been featured in these empirical studies as a potential influencing factor for policy responses. This is notable since the background of political leaders has been found to be a significant factor for, for instance, the level of a country's budget deficit (Hayo and Neumeier, ), the willingness to adopt reforms, specifically liberalization (Dreher et al ., ), and its preferences with regard to monetary policy (Göhlmann and Vaubel, ). Investigating whether the background of the political leadership makes reform more or less likely in times of crisis might open up a promising area of research.…”
Section: Methodological Operationalization Of the Crisis Hypothesis –mentioning
confidence: 99%
“…Similarly, Congleton and Zhang (2013) finds that US presidents with a higher human capital have better economic performance. Hayo and Neumeier (2016) uncover a relationship between leaders' socio-economic status and the debt-to-GDP ratio in OECD countries.…”
Section: Related Literaturementioning
confidence: 96%
“…Consequently, the female politicians in political bodies are relevant for the women's substantive representation (Phillips, 1998). While the Weberian theory devises a genderless manager, within sociological and psychological research, Hayo and Neumeier (2016) argue that specific aspects of leaders’ socioeconomic backgrounds, including gender, could affect the political decisions. In the real world, men and women bring different backgrounds and experiences in management of public institutions (Opstrup & Villadsen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Kisgen (2013) found that female leaders are more cautious when making financial decisions and that organizations with female leaders were less likely to issue debt. In the fiscal field, however, Hayo and Neumeier (2016) analyzed the relationship between the gender of leaders and government primary deficits in a sample of 21 OECD countries, and did not find any differences between male and female leaders.…”
Section: Introductionmentioning
confidence: 99%